Pengaruh Minat Terhadap Hasil Belajar Pendidikan Jasmani Pada Siswa SD - Bakar, Abu; Hidayat, Rachmat (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Learning interest plays an important role in determining students' learning outcomes, including in Physical Education subjects. The purpose of this study is to determine whether there is an influence of interest on Physical Education learning outcomes among students of SD Inpres Pattalassang, Gowa Regency. The research method employed is descriptive research, with interest as the independent variable and learning outcomes as the dependent variable. The population of this study consists of all students of SD Inpres Pattalassang, Gowa Regency. The sample includes 15 fifth-grade students from SD Inpres Pattalassang, Gowa Regency, identified as having low learning interest, all of whom were included in the study. Data analysis was performed using SPSS software. The results of the study concluded that there is a significant influence of learning interest on Physical Education learning outcomes among students of SD Inpres Pattalassang, Gowa Regency, amounting to 88.2%.